2017
DOI: 10.1038/s41598-017-12927-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum specific helicase 3 is nucleocytoplasmic protein and unwinds DNA duplex in 3′ to 5′ direction

Abstract: Plasmodium falciparum is responsible for most dangerous and prevalent form of malaria. The emergence of multi drug resistant parasite hindered the prevention of malaria burden worldwide. Helicases are omnipresent enzymes, which play important role in nucleic acid metabolism and can be used as potential targets for development of novel therapeutics. The genome wide analysis of P. falciparum 3D7 strain revealed some novel parasite specific helicases, which are not present in human host. Here we report the detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 64 publications
(68 reference statements)
0
18
0
Order By: Relevance
“…The subcellular localization of PfPSH1 was studied with the help of immunofluorescence microscopy, and it is majorly present in the cytoplasm and partially in the nucleus of the parasite in all the intraerythrocytic developmental stages. It has been previously reported that PfPSH2 and PfPSH3 are localized in both nucleus and cytoplasm in intraerythrocytic developmental stages .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The subcellular localization of PfPSH1 was studied with the help of immunofluorescence microscopy, and it is majorly present in the cytoplasm and partially in the nucleus of the parasite in all the intraerythrocytic developmental stages. It has been previously reported that PfPSH2 and PfPSH3 are localized in both nucleus and cytoplasm in intraerythrocytic developmental stages .…”
Section: Discussionmentioning
confidence: 95%
“…PfPSH1CM shows loss in ATPase activity, and similarly, helicase activity of the mutant was also abrogated. PfPSH1 is unique in requirement of nucleotide triphosphate when compared to other PSHs (PfPSH2 and PfPSH3); it prefers CTP more than UTP and ATP to unwind DNA, whereas PfPSH2 and PfPSH3 prefer only ATP [19,20]. Despite having similar core and signature motifs various helicases behave differently, previous reports suggest that PfWrn prefers GTP than ATP to unwind DNA and PfUvrD has no preference, and it can unwind well with all four NTPs [32,35].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations